Hablando de sexo y de placer. Palabra de poetas latinoamericanas - Fariña Busto, María Jesús (Romanica Silesiana, 2021)
This paper highlights the way in which some Latin American women poets from different decades of the twentieth century, and from different countries, approached the territory of desire and pleasure, at times vindicating it by revealing how patriarchal culture denied them their expression, both in life as in literature, at other times, simply and decisively, proclaiming it without any kind of restriction. To this goal, significant examples of poetic approaches, emphases, and different tones are provided throughout the article.